ANALYSIS OF THE RELIEF STORY OF JAJAGHU TEMPLE AS A MEANS OF INSTILLING MORAL VALUES IN STUDENTS - Lailatul Fitriyah (History Education, University of Jember, 2025)
Education is an important aspect for instilling moral values in students, one of which is through history lessons. History lessons play a strategic role in instilling moral values in students through historical traces. Historical traces contain stories that contain important values to be taught to students, one of which is Jajaghu Temple. Jajaghu Temple or Jago Temple is a temple site left behind by the 13th-century Singhasari Kingdom, which has narrative reliefs rich in religious and mythological stories. The purpose of this study is to analyse the stories in the reliefs of Jajaghu Temple to identify moral values that can be instilled in students. This study uses a historical method consisting of five stages, namely topic selection, heuristics, verification, interpretation, and historiography. The results of the discussion show that Jajaghu Temple is a historical relic from the Hindu-Buddhist Kingdom era, which remains a source of history to this day. It is evident that Jajaghu Temple preserves important stories through its reliefs, namely the story of the crane and the turtle, the story of Ari Dharma, the story of Kunjarakarna (heaven and hell), the story of Partayatna, the story of Arjunawiwaha, and the story of Kresnayana. The story has the potential to instil moral values in students, enriching their character education as part of their cultural and moral heritage and preparing them to face the challenges of the future.